Development of a Definition for Medical Affairs Using the Jandhyala Method for Observing Consensus Opinion Among Medical Affairs Pharmaceutical Physicians - Jandhyala, Ravi (Frontiers in Pharmacology, 2022)
Background: There is currently no standard definition of medical affairs, despite its increasing importance to the pharmaceutical industry. The evolution of medical affairs necessitated the development of a standardised definition to guide policy and practice to ensure that patients’ interests remain central amid shifts that have, in the past, created fertile ground for ethical violations. Objectives: The aim of this study was to use an empirical method to observe a consensus of expert opinion on the definition of medical affairs to guide policy and practice within this function. Methods: In total, 11 medical affairs pharmaceutical physicians (MAPPs) completed a qualitative online survey to identify a list of key items to define medical affairs using the Jandhyala method for generating a consensus of expert opinion. Responses were coded and scored, and aggregated responses were presented to participants in a consensus round. Participants rated their agreement with each item on a 5-point Likert scale from strongly agree to strongly disagree. Indicators that reached a consensus index of > 50% (CI > = 0.51) were retained. Items were categorised per previously defined medical affairs functions to determine the scope of the definition. A comparative content analysis using a previous definition identified in the literature was conducted to determine the utility of the definition generated here. Results: In total, 11 MAPPs generated 15 unique items to define medical affairs. Item awareness indices ranged from 0.24 to 1.00. All items had a CI of more than 0.5 and were included in the final definition. All items could be categorised per previously defined medical affairs functions. Comparative content analysis showed that our definition varied in four ways: the designation of medical affairs as a medical specialty, the leadership of medical affairs in medicine adoption, the generation of real-world evidence and the specification of distinct stakeholders who benefit from medical affairs. Conclusions: A standard definition of medical affairs that incorporates the key principles of medical affairs as a medical specialty that leads medicine adoption and generates real-world evidence for specific stakeholders may protect and further the interests of patients by governing practice and policy.